Reassessing Blacklist Era Television: Civil Libertarianism in "You Are There," "The Adventures of Robin Hood," and "The Buccaneers" - Paul, Andrew (American Studies, 2015)
This article examines three popular scripted television shows of the 1950s, You Are There, The Adventures of Robin Hood, and The Buccaneers, all of which were clandestinely written by victims of the anti-communist blacklist in the American entertainment industry. I argue that although these shows have been conceived as methods of “resistance” by both the writers themselves and the historians that have studied them, the programs participated in a discursive process that saw the emergence of a dominant civil libertarian rhetoric in postwar culture. Replacing the wartime left-liberal lexicon of civil rights and social and economic justice, the civil libertarianism of the 1950s represented not simply resistance, but also a common governmentalizing language by which marginalized leftists and empowered anti-communists alike could celebrate liberalism as an antidote to forms of totalitarian rule.